Hybrid OCDMA over WDM system using modified double weight (MDW) code for optical access network - Nasim, Ahmed; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Hilal Adnan, Fadhil, Dr.; R. Badlishah, Ahmad, Prof. Madya Dr.; Mohd Abdur, Rashid, Dr. (Trans Tech Publications, 2012)
Link to publisher's homepage at http://www.ttp.net/